Endoplasmic reticulum-localized circular RNA FAM13B restrains nasopharyngeal carcinoma lymphatic metastasis through downregulating XBP1 - Guo-Dong Jia; Si-Yi Xie; Xiao-Yun Li; Liang-Ji Li; Jing Jin; Li-Ting Liu; Xue-Song Sun; Sai-Lan Liu; Qiu-Yan Chen; Lin-Quan Tang; Li Yuan; Hai-Qiang Mai (Journal of Experimental & Clinical Cancer Research)
Abstract Background Nasopharyngeal carcinoma (NPC) is often diagnosed at an advanced stage due to its hidden location, with 70–80% of patients presenting with cervical lymph node metastasis. This high metastasis rate is a major cause of treatment failure and mortality. Non-coding RNAs, particularly circRNAs, have emerged as key players in tumor development, but their roles in NPC lymph node metastasis and angiogenesis remain unclear. This study aimed to identify key circRNAs involved in NPC lymph node metastasis and elucidate their mechanisms of action. Methods We identified circFAM13B, a differentially expressed circRNA, using transcriptome sequencing of nasopharyngeal tissues from patients with and without lymph node metastasis. Stable cell lines with circFAM13B overexpression and knockdown were constructed. Functional experiments, including cell invasion, migration, and metastasis assays, were performed in vitro and in vivo. Mechanistic studies involved RNA sequencing, RNA pull-down, and RNA immunoprecipitation assays to explore interacting proteins and signaling pathways. Results CircFAM13B was downregulated in metastatic tissues and localized in the endoplasmic reticulum (ER). It acted as a tumor suppressor by binding to RBM3 and promoting degradation of uXBP1 mRNA, a key ER stress molecule. This interaction downregulated sXBP1 and CST6, inhibiting lymphangiogenesis and metastasis. Reduced CST6 expression was associated with poor prognosis in NPC. Conclusions Our study reveals that circFAM13B inhibits ER stress-related pathways in NPC, highlighting its potential as a therapeutic target for lymph node metastasis.